Exploring determinants of hand hygiene compliance in LTCFs: a qualitative study using Flottorps’ integrated checklist of determinants of practice - Lescure, Dominique (Antimicrob Resist Infect Control, 2021)
BACKGROUND: Elderly residents in long-term care facilities (LTCFs) are vulnerable to healthcare-associated infections. Although hand hygiene is a leading measure for preventing infection, the compliance of healthcare workers is low. The aim of this study is to identify determinants that influence hand hygiene compliance of nursing staff in LTCFs. This information on determinants can eventually be used to develop a tailored implementation strategy for LTCFs. METHODS: This is an explorative, descriptive study using qualitative methods. We performed semi-structured focus group discussions with 31 nurses and nurse assistants from five Dutch LTCFs. Our focus group discussions continued until no new information could be identified from the data. We used Flottorps’ comprehensive checklist for identifying determinants of practice (the TICD checklist) to guide data collection and analysis. The audiotapes were transcribed verbatim and two authors independently analysed the transcripts with Atlas.ti software. RESULTS: LTCFs for the elderly have setting specific determinants that are decisive in explaining hand hygiene compliance. Most of these determinants are related to the residents with whom nurses build close relationships and for whom they want to create a homelike atmosphere. Residents can complicate the provision of care with unpredictable behaviour, being unwilling to receive care or use shared facilities. Our study also discovered setting-transcending determinants related to knowledge, professional interactions, guidelines, and incentives/resources. CONCLUSIONS: Nurses in LTCFs are constantly pursuing a balance between working hygienically, responding adequately to acute care needs, and maintaining a homelike environment for their residents. As a result, setting-specific determinants affect hand hygiene compliance, as do the known determinants that are important in other care settings. To improve compliance in LTCFs, interventions should be selected on a theoretical base while linking these determinants to change interventions. TRIAL REGISTRATION: Registration number 50-53000-98-113, Compliance With Hand Hygiene in Nursing Homes: Go for a Sustainable Effect (CHANGE) on ClinicalTrials.gov. Date of registration 28-6-2016.